Inventive engineering knowledge and skills for creative engineers - Arciszewski, Tomasz (CRC Press, Taylor & Francis Group, CRC Press is an imprint of the Taylor & Francis Group, an informa business, 2016)
"Inventive Engineering is an emerging engineering sci focused on the conceptual designing processes whereby